Learning Innovation Online Course Based on Blended Learning for Interactive Learning in The Era of Education 4.0 - Andika Bagus Nur Rahma Putra; Awalia Habibatuz Zahro; Amat Mukhadis; Nurul Ulfatin; Muhammad Ashar (Universitas Negeri Malang, 2019)
The objectives of this study: (1) developing online learning innovations based on blended learning for interactive learning media era education 4.0; and (2) testing the attractiveness of the product being developed. The development of Quipper School learning tools follows the 4-D model (namely defining, designing, developing, and disseminating). The results of this study include: (1) quipper school has several advantages to help the learning process, including students being able to learn independently, learning that is fun and interesting through features, displaying material and varied videos, students can practice questions, and teachers can monitor the progress of student learning; (2) Quipper School media which is proven to improve student learning outcomes